Effect of Leverage on Profit Growth in Manufacturing Companies in the Consumer Goods Sector Listed on the Indonesia Stock Exchange (IDX) in 2015 - 2019 - Irene Sukma Lestari Barus; Muhammad Adhi Rusdi; Apriwandi Apriwandi; Dyah Purnamasari (Transpublika Publisher, 2025)
The main goal of this study is to examine how leveraging affects the increase in profits in the Consumer Goods Industry Sector of manufacturing firms that are publicly traded on the Indonesia Stock Exchange (IDX) between 2015 and 2019. The study is driven by the inconsistency in company performance, with fluctuations in profit growth and leverage. Data collection for this study is conducted through documentation. The sample selection method employed is purposive sampling, with a total of 23 manufacturing companies from the consumer goods industry sector on the Indonesia Stock Exchange (IDX) during 2015-2019. The technique used for analysing the data involves conducting a panel data regression analysis with a significance level of 5%, using Program Eviews 12. According to the results, it appears that the level of debt does not have a direct effect on the increase in profits for manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange (IDX) from 2015 to 2019. However, it was observed that both leverage and Company Size collectively influence profit growth in such companies during the same period.